Changes in outcomes over time in intermediate‐risk patients treated for severe aortic stenosis. Issue 12 (5th October 2020) - Khalil, Khalil N.; Boukhris, Marouane; Badreddine, Malek; Ben Ali, Walid; Stevens, Louis‐Mathieu; Masson, Jean‐Bernard; Potvin, Jeannot; Gobeil, Jean‐François; Noiseux, Nicolas; Khairy, Paul; Forcillo, Jessica
Abstract: Background: The advent of transcatheter aortic valve replacement (TAVR) has changed the practice of treating patients with severe aortic stenosis (AS). Heart‐Teams have improved their decision‐making process to refer patients to the best and safest treatment. The evidence allowed centers to increase funding and TAVR volume and extend indications to different risk categories of patients. This study evaluates the outcomes of intermediate‐risk patients treated for severe AS in an academic center. Methods: Between 2012 and 2019, 812 patients with AS underwent TAVR or surgical aortic valve replacement (SAVR). A propensity score‐matching analytic strategy was used to balance groups and adjust for time periods. Outcomes were recorded according to the Society of Thoracic Surgeons Guidelines; the primary outcome being 30‐day mortality and the secondary outcomes being perioperative course and complications. Results: No difference in mortality was seen but complications differed: more postoperative transient ischemic attacks, permanent pacemaker implantations, and perivalvular leaks in the transcatheter group, while more acute kidney injuries, atrial fibrillation, delirium, postoperative infections and bleeding, tamponade and need for reoperation in the surgical group as well as a longer hospital length‐of‐stay. However, over the years, morbidities/mortality decreased for all patients treated for AS. Conclusions: Data showed an improvement in morbidities/mortality for intermediate‐risk patients treated with SAVR or TAVR. Increased funding allowed for a higher TAVR volume by increasing access to this technology. Also, the difference in complications could impact healthcare costs. By incorporating important metrics such as length‐of‐stay, readmission rates, and complications into decision‐making, the Heart‐Team can improve clinical outcomes, healthcare economics, and resource utilization.